Education And Training Centre At Science And Techno Park USU Kwala Bekala - Nasution, Achmad Delianur; Puteri, Shafira Najwa (Jurnal Koridor, 2020)
Education and Training Center is a place where all activities to give, obtain, improve, and develop work competencies, productivity, discipline, attitude, and work ethic at a certain level of skills and expertise by the qualifications of a job or a job. (UU RI, 2003). The method is to create an Education and Training Centre. Education and Training center society as informal education in improving competence or quality for individuals. The Education and Training center is one of the most important buildings in the USU Kwala Bekala Campus. The USU Kwala Bekala campus divided into several zones. The entrance zone is the main gate that describes the initial image of the USU Kwala Bekala campus. This zone designed with the concept of Science & Technology Park. Because the site location located in the entrance zone, the building design as "Building as A Gate," where the building is designed to create the impression of the entrance on the site. Then, at the main entry point, it was strengthened by the existence of a vista that led to USU's reservoirs and guesthouse. The building is also designed to integrate with the surrounding buildings. The design in STP built with the concept of green architecture. With the green architecture concept, the building will be more environmentally friendly for public health. Some things that considered in green architecture are the concept of energy saving. This project will explain how to design an education and training center by applying the green architecture theme to the STP area in USU Kwala Bekala